Best Answer

x2 + 4x - 60 factors into (x + 10)(x - 6). You can use the FOIL method to check your answers when you factor.

Q: What is the factor of this trinomial x2 plus 4x - 60?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

use the quadratic formula since there isn't a factor of 60 that when added together equals 19 The above answer is wrong because 4 and 15 are such numbers. x2 + 19x + 60 = x2 + 4x + 15x + 60 = x(x + 4) + 15(x + 4) = (x + 4)(x + 15)

4x+35-2x+25 = 6 2x+60 = 6 2x = 6-60 2x = -54 x = -27

3x2 + 27x +60

9x = 60x = 60/9 = 6 2/3 (or 6.67)

Impossible to give a correct solution in the absence of any plus or minus signs.

Related questions

use the quadratic formula since there isn't a factor of 60 that when added together equals 19 The above answer is wrong because 4 and 15 are such numbers. x2 + 19x + 60 = x2 + 4x + 15x + 60 = x(x + 4) + 15(x + 4) = (x + 4)(x + 15)

You would factor out -1 (a) from a trinomial in an equation such as -a^2 +30a - 2a + 60 after the middle term has been separated. The final answer of this trinomial would then be (a-30) (a-30).

The answer is that there is no such x - unless you define "plus" in some special way.

yes because 4x 15 iss 60

x = 10

no 3x2=6 then 4x-15= -60 so 6 added with - 60 = -54

4x+35-2x+25 = 6 2x+60 = 6 2x = 6-60 2x = -54 x = -27

3x2 + 27x +60

4X + 7Y = 60 -4X + 7Y = - 4 -----------------------+ 14Y = 56 Y = 4 --------- insert back into one of these equations to find X 4X + 7(4) = 60 4X + 28 = 60 4X = 32 X = 8 ------------check 4(8) + 7(4) = 60 32 + 28 = 60 60 = 60 ----------------checks, now second equation -4(8) + 7(4) = -4 -32 + 28 = -4 -4 = -4 --------------checks solution set. X = 8 Y = 4 (8,4)

9x = 60x = 60/9 = 6 2/3 (or 6.67)

hi

-4x + 6y - 5z = 60At the x-intercept, 'y' and 'z' are zero:-4x = 60 ===> x = -15At the y-intercept, 'x' and 'z' are zero:6y = 60 ===> y = 10At the z-intercept, 'x' and 'y' are zero:-5z = 60 ===> z = -12